EVALUASI ALAT PENDUKUNG PADA MANAJEMEN PROYEK PERANGKAT LUNAK: UNTUK PENGEMBANGAN PERANGKAT LUNAK - Muhammad Andrean Hidayatullah; Ki Ageng Nasrokh Mangkunegara Putra; Muhammad 'Ainul Yaqin (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2024)
Software project management is a crucial aspect of effective and efficient software development. One of the main challenges in software project management is selecting the right support tools to ensure project success. This study evaluates various software project management support tools to identify the most effective tools based on specific criteria such as ease of use, features provided, integration with other tools, and technical support. The study proposes a solution by using a criteria-based evaluation methodology and then testing several popular tools such as Jira, Trello, Asana, Docker, and Microsoft Project. The experimental results show that Jira proved to be the best choice with the highest overall score. However, Asana and Microsoft Project also performed well in certain categories, while Docker and Trello tended to score lower. These results indicate that the selection of project management tools should be based on a careful analysis of the specific needs of the project and the most important criteria for the team involved. Therefore, the successful implementation of support tools depends on a deep understanding of the software development process, team dynamics, and strong management skills.